2003
DOI: 10.1093/treephys/23.3.211
|View full text |Cite
|
Sign up to set email alerts
|

Early selection improves clonal performance and reduces intraclonal variation of Norway spruce plants propagated by somatic embryogenesis

Abstract: Height growth during the first and second growth periods (i.e., the June-September period in consecutive years) and intraclonal variation were assessed in 13 Norway spruce (Picea abies (L.) Karst.) clones propagated by somatic embryogenesis. The plants were acclimatized and grown in a greenhouse until mid-July and then transferred outdoors. The clonal mean heights after the first and second growth periods were lower for somatic embryo plants than for seedlings from corresponding families sown at the time of so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
6

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 11 publications
0
20
0
6
Order By: Relevance
“…In micropropagation of coniferous trees, an elimination of auxins and cytokinins from the medium and addition of ABA as well as an increase in osmotic pressure at the stage of maturation of somatic embryos, are necessary for regeneration of cotyledonary embryos. Many researchers found that addition of exogenous ABA to the medium in a suitable concentration affects the number of mature somatic embryos in various species of coniferous trees (Norgaard 1997;Label and Lelu 2000;Percy et al 2000;Stasolla et al 2002;Hogberg et al 2003). Reactions of embryogenic tissues of coniferous trees to ABA are highly varied.…”
Section: Maturation Of Somatic Embryosmentioning
confidence: 99%
“…In micropropagation of coniferous trees, an elimination of auxins and cytokinins from the medium and addition of ABA as well as an increase in osmotic pressure at the stage of maturation of somatic embryos, are necessary for regeneration of cotyledonary embryos. Many researchers found that addition of exogenous ABA to the medium in a suitable concentration affects the number of mature somatic embryos in various species of coniferous trees (Norgaard 1997;Label and Lelu 2000;Percy et al 2000;Stasolla et al 2002;Hogberg et al 2003). Reactions of embryogenic tissues of coniferous trees to ABA are highly varied.…”
Section: Maturation Of Somatic Embryosmentioning
confidence: 99%
“…For the same species, Cyr et al (1991) reported that the differences between somatic plants and seedlings occurred early during plant development. Although somatic plants were consistently shorter than seedlings after the first growth period, the differences in height decreased by the end of the second growth period (Högberg et al 2003). In contrast, for coastal Douglasfir (Pseudotsuga menziesii var.…”
Section: Discussionmentioning
confidence: 90%
“…Evidences that culture conditions during somatic embryo development may reduce the growth of somatic plants were reported for several conifers (Högberg et al 2003). Use of PEG and long-term contact with ABA during maturation substantially reduced the growth of regenerated Norway spruce plants von Arnold 1998, Högberg et al 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For in vitro cloning technologies, the selection differential, juvenile mature cor relations and the reciprocal of the generation interval are major factors in saving time and capturing genetic gains elite clones were established in the greenhouse for field testing. In Europe, clones produced from PEMs have been field tested for spruce, pine, and other conifers (e.g., Högberg et al, 2003). In North and South America, South east Asia, and New Zealand, sever al industries and governments have scaled up the production of 'somatic seedlings' to commercial volumes.…”
Section: Fig 8 Capturing Genetic Gains (G)mentioning
confidence: 99%